2019
DOI: 10.1071/wf18171
|View full text |Cite
|
Sign up to set email alerts
|

Determining the sensitivity of grassland area burned to climate variation in Xilingol, China, with an autoregressive distributed lag approach

Abstract: We examined the relationship between climate variables and grassland area burned in Xilingol, China, from 2001 to 2014 using an autoregressive distributed lag (ARDL) model, and describe the application of this econometric method to studies of climate influences on wildland fire. We show that there is a stationary linear combination of non-stationary climate time series (cointegration) that can be used to reliably estimate the influence of different climate signals on area burned. Our model shows a strong relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
(76 reference statements)
0
10
1
Order By: Relevance
“…This study demonstrates that in the long-run, grassland area burned in Xilingol is more sensitive to changes in wind speed and temperature than other climate variables [10,15,36]. Past…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This study demonstrates that in the long-run, grassland area burned in Xilingol is more sensitive to changes in wind speed and temperature than other climate variables [10,15,36]. Past…”
Section: Discussionmentioning
confidence: 73%
“…Understanding how climate influences fire in grasslands is challenging because of complex interactions between climate parameters, ignitions, and past fire history [3][4][5][6][7][8][9][10][11][12][13]. Previous research has demonstrated complex relationships between fire activity and climate variability in the extensive grasslands of Xilingol in northern China [14,15]. Fire in this region potentially creates feedbacks between climate and fire occurrence both by climate forcing related to carbon emissions from fires and changes in flammability related to post-fire succession [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Increased grazing constrains grassland burning leading to an "area burned deficit". Otherwise, the system is highly responsive to high-speed seasonal winds with low relative humidity, quickly drying fuel, and increasing the potential for extensive grassland fires across the region 28,42 .…”
Section: Simulation and Analysis Of Ardl Dynamicsmentioning
confidence: 99%
“…Therefore, fire season fuel moisture levels are accordingly unresponsive to precipitation variation. Third, the vast majority of fires in Xilingol originate from human activities 23,28,42 . These ignitions, and wind speeds and temperatures coincident with them, rather than fuel conditioning, may explain burned grassland extent.…”
Section: Impacts Of Burned Grasslands To Carbon Emissions and Ecologimentioning
confidence: 99%
See 1 more Smart Citation